PENGARUH PENGGUNAAN METODE STEAM TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN DI KOBER AL HIDAYAH - Susanti, Susi; Hidayat, Yusuf; Sarip, Sri Kurnia (LPPM IAD Probolinggo, 2025)
This study investigated the effectiveness of the Science, Technology, Engineering, Art, and Mathematics (STEAM) method in enhancing the early childhood’s cognitive development of 4-5 years old at Kober Al Hidayah. The STEAM method emphasizes the interconnectedness of knowledge and skills. This study employed a quantitative method under pre-experimental design. The findings of the study found that before being given the implementation of the STEAM method, the early childhood’s cognitive development of 4-5 years old at Kober Al Hidayah showed